Prospective Memory Performance in Simulated Air Traffic Control: Robust to Interruptions but Impaired by Retention Interval. (December 2020) - Wilson, Michael David; Strickland, Luke; Farrell, Simon; Visser, Troy A. W.; Loft, Shayne
Objective: To examine the effects of interruptions and retention interval on prospective memory for deferred tasks in simulated air traffic control. Background: In many safety-critical environments, operators need to remember to perform a deferred task, which requires prospective memory. Laboratory experiments suggest that extended prospective memory retention intervals, and interruptions in those retention intervals, could impair prospective memory performance. Method: Participants managed a simulated air traffic control sector. Participants were sometimes instructed to perform a deferred handoff task, requiring them to deviate from a routine procedure. We manipulated whether an interruption occurred during the prospective memory retention interval or not, the length of the retention interval (37–117 s), and the temporal proximity of the interruption to deferred task encoding and execution. We also measured performance on ongoing tasks. Results: Increasing retention intervals (37–117 s) decreased the probability of remembering to perform the deferred task. Costs to ongoing conflict detection accuracy and routine handoff speed were observed when a prospective memory intention had to be maintained. Interruptions did not affect individuals' speed or accuracy on the deferred task. Conclusion: Longer retention intervals increase risk of prospective memory error and of ongoing task performance being impaired by cognitive load; however, prospective memory can be robust to effects of interruptions when the task environment provides cuing and offloading. Application: To support operators in performing complex and dynamic tasks, prospective memory demands should be reduced, and the retention interval of deferred tasks should be kept as short as possible.